Effects of leadership style on coach-athlete relationship, athletes’ motivations, and athlete satisfaction - Jin, Hao; Kim, Seungmo; Love, Adam; Jin, Yun; Zhao, Jie (Frontiers in Psychology, 2022)
The current study investigated the impacts of autocratic and democratic leadership styles leadership style on the coach-athlete relationship, athletes' motivations, and athlete satisfaction. Survey data were collected from 298 student-athletes (male = 157; 52.7%, female =141; 47.3%) from 20 different Chinese collegiate sports. The results indicated democratic leadership had a direct positive influence on the coach-athlete relationship, while autocratic leadership had no direct effect. Both leadership styles did not influence autonomous motivation. The coach-athlete relationship, meanwhile, had a full mediation effect between democratic leadership and athletes’ motivation and satisfaction. In addition, autonomous motivation had a partial mediation effect between the coach-athlete relationship and athlete satisfaction. Ultimately, the results underscore the need for coaches and administrators to understand the impact of different leadership styles and highlight the importance of democratic leadership in improving athletes’ psychological outcomes.